Educational factors enabling the new students to survive and thrive - Adi Suryani; Soedarso Soedarso (International Journal of Evaluation and Research in Education (IJERE), 2022)
Entering higher education and starting new living can be challenging for new students. They need many information to integrate themselves to new communities and conform to new organizational culture, systems and programs. Organizational socialization is one of several socialization options which may promote the new students’ adjustment process, facilitate their learning process to survive and thrive. Despite the important role of organizational socialization, it is still under-examined in educational sector. Thus, this study analyzed educational factors enabling the new students to educationally survive and thrive. The data were collected through 22 new students’ narrative texts, freely voicing their experiences in higher education at their first semester. The data were analyzed by employing thematic, within-and-cross case analysis, underpinned by interpretivism paradigm. The study found that the new students’ educational survival and thriving needs the elaboration of organizational, social and emotional experiences into academic determination. Thus, the study challenged the dominant power of academic rigor in determining the educational thriving. Instead, the study suggested the new defined educational thriving concept by recognizing the roles of social, organizational and emotional roles, as presented in the reconstructed educational thriving triangle model.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//